The Pedagogical Model as a Strategy for the Development of Greater Life Satisfaction - Arguiñano-Madrazo, Andoni (2025)
Objective. This paper aims to evaluate whether a referral school in Antzuola, Spain, whose pedagogical project is focused on the student wellbeing, has influenced satisfaction with life (SWL) of its alumni as adults. Method. A quantitative methodological approach is used to measure SWL and other variables in a sample of 268 former students who attended the school between 1975 and 2001. After verifying the internal consistency of the data, analyses were conducted to examine whether SWL varied according to different variables, using independent-samples t-tests and ANOVA. Results. The results indicate that SWL is higher among alumni over 35 years of age, those who have had children, those who have received greater support from teachers, those with more social relationships, higher self-esteem and greater self-perception regarding the level of emotional education. Conclusions. This study concludes that, in addition to preparing students to respond satisfactorily to the requirements of formal education, the pedagogical model studied has proven to be an institution with an educational approach capable of preparing students for happiness in a world in constant transformation.